Optimal Management of a Research and Development Project - Lucas, Robert E. (Management Science, 1971)
This paper offers a series of models designed to aid in the evaluation and control of an individual research and development project. The project under consideration is assumed to involve costs incurred over a period [0, T] and a return earned at T (or discounted to T) when the project is completed. In two of the models discussed below, the completion time T is regarded as known; in two others, T is taken to be a random variable with a known distribution. In two models, the costs per unit of time of operating the project are assumed to be fixed; in the other two, costs are variable, with increased expenditure resulting in a decreased completion time. Each of the four possible combinations of assumptions is treated in a separate section. The last section contains a summary and discussion of results.